THE IMPLEMENTATION OF GOVERNMENT AUTHORITY IN RELATION TO THE SPORTS POLICY OF MALUKU PROVINCE GOVERNMENT - Albertus Fenanlampir; Rahmat Hidayat (EDU SCIENCES JOURNAL, 2020)
The development of sports in Maluku in its implementation is always based on Law Number 3 of 2005 concerning the National Sports System, that "Local Governments have the authority to regulate, foster, develop, implement, and supervise the implementation of sports in the regions". This means that the government based on institutional functions is given full authority as a policy maker. The purpose of this study is to describe the extent of the Implementation of Government Authority to the Sports System in Maluku Province. The results of the study found: (1) That the sports policy in Maluku has not been a priority in regional development and in its implementation delegated to the relevant agencies / organizations / federations. (2) The role of the Maluku provincial government in sports development is divided into three scopes, namely educational sports, recreational sports and achievement sports. Guidance on recreational sports and educational sports is handled and managed by the Department of Youth and Sports (DISPORA) in coordination with the Department of Education and Culture (DISDIKBUD), the Federation of Indonesian Community Recreational Sports (FORMI) and the National Paralympic Commission (NPC) Maluku to synergize programs from the center to the center to region. Whereas the fostering and development of sports achievements are bestowed and implemented by KONI Maluku and its members. (3) That the Maluku provincial government provides operational assistance with the APBD, through DIPA SKPD and Grants to agencies / organizations / federations namely achievement sports through KONI, Sports education through DISDIKBUD and DISPORA in coordination with FORMI and NPC Maluku. (4) The Government Oversight Function on the implementation of sports in Maluku is carried out in two ways, namely internal and external. Internal supervision is carried out by sports institutions to achieve consistency between policies and implementation, while external supervision by the Inspectorate and the Financial Supervisory Agency (BPK) to ensure the use of the budget is on target and in accordance with reporting.